Experimental and numerical analysis of solar still using Pyrex glass quantum dot in tropical climate - Singh P.K.; Rathore P.K.S.; Shukla S.K. (My University, 2025)
This study investigates the effect of using quantum dots (QDs) on the performance of solar still in the tropical climate of India. This article presents a new way to use QDs, which on absorbing solar energy increases water evaporation rate. Pyrex glass powder QDs are used in the solar still due to its high absorptivity value. An experimental setup of solar still with QD and without QD was developed, and a comparative analysis was conducted under the real outdoor environment in a tropical climate. The experimental results were also validated through mathematical modeling. The experiment was carried out by mixing Pyrex glass powder QDs with black paint and was coated on the basin and sidewalls of the solar still. Experiments were conducted for a depth of 0.02 m for solar still with QDs and without QDs. The results revealed that for 0.02 m of water depth and 1 m2 of basin area, the percentage increase in distillate output using Pyrex glass powder QDs is 29.36% experimentally and 29.94% theoretically. Furthermore, the net percentage increase in solar still efficiency by using Pyrex glass QDs is 74.74% experimentally and 61.03% theoretically. The study analyzed that all the experimental results are in good agreement with the theoretical analysis. The addition of Pyrex glass powder QDs and black paint mixture in the basin of solar still caused significant enhancement in the distillate output and solar still efficiency. © 2021 John Wiley & Sons Ltd.